Comparative evaluation of a novel multisensor device EYVA versus standard clinical sphygmomanometry for blood pressure measurement: a paired observational study - Kiron, Varsha; Navuluri, Sumanth K.; Nadiminti, Chandra S. (International Journal of Research in Medical Sciences, 2026)
Background: Reliable and accessible blood pressure (BP) monitoring is vital for effective hypertension management. EYVA, a novel multisensor device, aims to provide accurate, non‑invasive BP measurement. We evaluated EYVA’s accuracy compared with standard clinical sphygmomanometry. Methods: A paired observational study involving 442 adult participants was conducted from June 2022 to August 2022. Blood pressure was sequentially measured using EYVA and a standard-of-care (SOC) sphygmomanometers under resting conditions. Paired t‑tests, Pearson correlation and Bland-Altman analyses assessed agreement and consistency between methods. Results: EYVA showed strong agreement with standard of care (SOC) for both systolic and diastolic BP. Mean systolic BP was 127.69±16.29 mmHg with EYVA and 126.77±16.90 mmHg with SOC, with a bias of 0.93 mmHg (p<0.001) and Pearson correlation r=0.94. Diastolic BP averaged 84.19±11.74 mmHg (EYVA) and 83.45±12.48 mmHg (SOC), with a bias of 0.74 mmHg (p<0.001) and correlation r = 0.95. Bland-Altman analysis indicated limits of agreement of ±11.25 mmHg for systolic and ±7.64 mmHg for diastolic measurements. Conclusions: The EYVA device demonstrates clinically acceptable agreement with standard BP measurements, supporting its utility for clinical and home‑based BP monitoring.